2014
DOI: 10.2334/josnusd.56.235
|View full text |Cite
|
Sign up to set email alerts
|

Accidental ingestion of an air-water syringe tip during routine dental treatment: a case report

Abstract: Accidental ingestion of instruments ortheir components is a possible complication of dental treatment. Although in many cases the foreign object can pass through the gastrointestinal tract without any need for surgical intervention to retrieve it, sometimes such incidents can be life-threatening. This paper reports a case of accidental ingestion of an airwater syringe tip during routine dental treatment for which endoscopic retrieval was required. The present case highlights the need for dental professionals t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…1,10 Pilnej interwencji wymaga również połknięcie dużego przedmiotu, którego pasaż przez cały przewód pokarmowy jest niemożliwy. 11,12 Należy pamiętać, że opisywane komplikacje nie występują jedynie podczas wizyty w gabinecie dentystycznym, ale także w dowolnym czasie, nawet po wielu latach od zaistnienia takiej sytuacji połknięcia ciała obcego przez pacjenta. Odcementowanie uzupełnień protetycznych, m.in.…”
Section: Occurrence Of Aspirations and Ingestions In Dental Practiceunclassified
See 1 more Smart Citation
“…1,10 Pilnej interwencji wymaga również połknięcie dużego przedmiotu, którego pasaż przez cały przewód pokarmowy jest niemożliwy. 11,12 Należy pamiętać, że opisywane komplikacje nie występują jedynie podczas wizyty w gabinecie dentystycznym, ale także w dowolnym czasie, nawet po wielu latach od zaistnienia takiej sytuacji połknięcia ciała obcego przez pacjenta. Odcementowanie uzupełnień protetycznych, m.in.…”
Section: Occurrence Of Aspirations and Ingestions In Dental Practiceunclassified
“…1,10 The ingestion of large object, whose passage through the entire digestive tract is impossible, also requires urgent intervention. 11,12 It should be remembered that the complications described above may not occur only during a visit to the dentist's office, but also at any time, even after many years from the occurrence of such a situation like ingestion by the patient. Debonding of prosthetic restorations, including posts is the most frequently reported complication that the patient potentially should be informed about.…”
Section: Diagnostykamentioning
confidence: 99%
“…It has also been reported that inter-occlusal devices used for the restoration of occlusion, [7] air-water syringe tips, [8] endodontic instruments including dental clamps, [9] hand files or reamers, [10] hypodermic needles, [11] apex locator lip clips, [12] orthodontic brackets and/appliances, [13] and implant components [14] have been aspirated.…”
mentioning
confidence: 99%